MULTIPLE FRACTURES IN A SINGLE UPPER EXTREMITY: HUMERAL SHAFT, OLECRANON, DISTAL RADIUS AND FOURTH METACARPAL BONE FRACTURES IN AN ELDERLY PATIENT AFTER A FALL: A CASE REPORT - Serkan Bayram; Lezgin Mert; Mehmet Ekinci; Turgut Akgül; İrfan Öztürk (İstanbul Tıp Fakültesi Dergisi)
Floating limb is a complicated injury and is associated with limb deformation and increased morbidity and mortality. We report a rare case of a floating upper limb in a 77-year old woman with ipsilateral humeral shaft, olecranon, distal radial and metacarpal bone fractures after a simple fall. The patient underwent surgery for humerus shaft, olecranon, and distal radius and was treated surgically with the 4th metacarpal conservative method. At the final follow-up 3 years after surgery, the patient had no complaints, all fracture had healed completely and elbow-wrist range of motion was complete. We discuss the surgical procedures that we used for the fractures, the mechanism of injury and the functional and radiological results. Multiple bone fractures in the same limb are rare and typically associated with high-trauma. We reported a unique case of an elderly patient with osteoporosis having multiple fractures in the same extremity that occurred as a result of low-energy trauma.